Protective Effect of Dictyophora Polysaccharides on Sodium Arsenite-Induced Hepatotoxicity: A Proteomics Study - Hu, Ting; Shen, Liming; Huang, Qun; Wu, Changyan; Zhang, Huajie; Zeng, Qibing; Wang, Guoze; Wei, Shaofeng; Zhang, Shuling; Zhang, Jun; Khan, Naseer Ullah; Shen, Xiangchun; et al. (Frontiers in Pharmacology, 2021)
The purpose of this study is to understand the mechanism of sodium arsenite (NaAsO2)-induced apoptosis of L-02 human hepatic cells, and how Dictyophora polysaccharide (DIP) protects L-02 cells from arsenic-induced apoptosis. The results revealed that DIP pretreatment inhibited NaAsO2 induced L-02 cells apoptosis by increasing anti-apoptotic Bcl-2 expression and decreasing pro-apoptotic Bax expression. Proteomic analysis showed that arsenic treatment disrupted the expression of metabolism and apoptosis associated proteins, including ribosomal proteins (RPs). After pretreatment with DIP, the expression levels of these proteins were reversed or restored. For the first time, it was observed that the significant decrease of cytoplasmic RPs and the increase of mitochondrial RPs were related to human normal cell apoptosis induced by arsenic. This is also the first report that the protective effect of DIP on cells was related to RPs. The results highlight the relationship between RPs and apoptosis, as well as the relationship between RPs and DIP attenuating arsenic-induced apoptosis.